Risks of Light and Moderate Alcohol Use in Fatty Liver Disease: Follow‐Up of Population Cohorts - Åberg, Fredrik; Puukka, Pauli; Salomaa, Veikko; Männistö, Satu; Lundqvist, Annamari; Valsta, Liisa; Perola, Markus; Färkkilä, Martti; Jula, Antti (Hepatology (Baltimore, Md.), 2020)
Background and Aims The effects of alcohol use in nonalcoholic fatty liver disease are unclear. We investigated the impact of alcohol use in fatty liver disease on incident liver, cardiovascular, and malignant disease, as well as death. Approach and Results Our study comprised 8,345 persons with hepatic steatosis (fatty liver index >60) who participated in health‐examination surveys (FINRISK 1992‐2012 or Health 2000), with available data on baseline alcohol intake. Main exclusions were baseline clinical liver disease, viral hepatitis, ethanol intake >50 g/day, and current abstainers. Data were linked with national registers for hospital admissions, malignancies, and death regarding liver, cardiovascular, and malignant disease, as well as all‐cause death. Adjustment were for multiple confounders. Alcohol consumption showed a dose‐dependent risk increase for incident advanced liver disease and malignancies. Consuming 10‐19 g/day of alcohol in general or 0‐9 g/day as nonwine beverages doubled the risk for advanced liver disease compared to lifetime abstainers. In contrast, alcohol intake up to 49 g/day was associated with a 22%‐40% reduction of incident cardiovascular disease (CVD). We observed a J‐shaped association between alcohol intake and all‐cause death with a maximal risk reduction of 21% (95% confidence interval, 5%‐34%) at alcohol intake of 0‐9 g/day compared to lifetime abstainers. However, these benefits on CVD and mortality were only observed in never smokers. Alcohol intake >30 g/day yielded increased risk estimates for mortality compared to lifetime abstainers. In a subpopulation with longitudinal data, alcohol intake remained stable over time in >80% of subjects. Conclusions Even low alcohol intake in fatty liver disease is associated with increased risks for advanced liver disease and cancer. Low to moderate alcohol use is associated with reduced mortality and CVD risk but only among never smokers.